The development and validation of the Dementia Quality of Life Scale for Older Family Carers (DQoL-OC) - De Oliveira, Deborah Christina; Vass, Catherine D.; Aubeeluck, Aimee (Taylor & Francis, 2017)
Purpose: Little is known about how caregiving affects the quality of life (QoL) of older family carers and no dementia and age-specific QoL scale is available for use with this population. This study aimed to develop and validate a unique dementia caregiving- and age-specific tool – the ‘Dementia Quality of Life Scale for Older Family Carers’ (DQoL-OC).